PERANCANGAN RANGKAIAN KONTROL PENYETABIL TEGANGAN 220 VOLT KAPASITAS 500 VA - ., Zainuddin (IIB Darmajaya, 2012)
With the rapid development of electronics and computer technology, we had to exploit and utilize the development and advancement as much as possible. One of the utilization of that advances is using the electronics control assembly for garden lighting, water pump controller, and also the electricity safety control. Electricity safety control should be good in ordert to use computer. If the electricity is not safe, it will damage computer. Based on that fact, electricity safety become necessity. So that the author learn about electricity controller from PLN with 220V voltage, and 500VA capacity. In this case, author learn about an application of that tool as stabilizer. Key word: PLN, Volt, Stabilizer control